Myocardial interstitial fibrosis assessed by extracellular volume quantification is a determinant of symptoms in aortic valve regurgitation with preserved ejection fraction. (8th February 2021) - Arangalage, D; Pavon, AG; Hugelshofer, S; Rutz, T; Muller, O; Schwitter, J; Monney, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: According to current guidelines indication for surgery is straightforward with a class I recommendation in case of severe symptomatic aortic regurgitation (AR) and/or left ventricular ejection fraction (LVEF) decrease ≤50%. However, the management of patients with asymptomatic severe AR with preserved LVEF remains debated, with a cruel lack of prognostic factors to identify patients who may benefit from early intervention. An explanation to the absence of such factors is that the determinants of symptoms, a strong prognostic parameter, have been poorly identified. Beyond LV dilation and systolic dysfunction, which are both recognized prognostic factors in chronic AR, we hypothesized that interstitial myocardial fibrosis, as an early indicator of LV remodeling, may also influence the occurrence of symptoms. Cardiovascular magnetic resonance (CMR)-based myocardial extracellular volume (ECV) quantification by T1 mapping has emerged as a valuable tool to quantify diffuse myocardial fibrosis. Objective: To study the relationship between myocardial interstitial fibrosis quantified by T1 mapping and the symptomatic status of patients with chronic aortic valve regurgitation. Methods: We retrospectively included 38 consecutive patients with chronic, isolated, mild to severe AR who underwent a CMR at our institution. Exclusion criteria were the presence of any other heart condition that may induce myocardial fibrosis, ≥ mild associated valve disease, AR secondary to endocarditis, genetic, inflammatory or congenital disease except bicuspid aortic valve. T1 mapping of the basal segments was performed before and after contrast administration measuring native and post-contrast T1 relaxation time and ECV. Results: Mean age was 56 ± 20 years, 30 patients (79%) were males, and symptoms were reported in 11 patients (29%). Mean LVEF was 57 ± 9% and ≥50% in 30 patients (79%). Aortic valve regurgitation fraction (RF) was 25 ± 13%, ECV 0.27 ± 0.04%, indexed LV end-diastolic volume (LVEDVi) 98 ± 32 ml/m2, end-systolic volume (LVESVi) 46 ± 19 ml/m2, and LV mass 79 ± 21 g/m2. LVESVi (r = 0.41, p = 0.01), LVEF (r=-0.59, p = 0.0001), and ECV (r = 0.42, p = 0.008) were correlated with symptoms, whereas age (r = 0.16, p = 0.33), gender (r=-0.24, p = 0.15), LVEDVi (r = 0.28, p = 0.09), LV mass index (r = 0.08, p = 0.62), and RF (r = 0.31, p = 0.06) were not. In the subgroup of patients with preserved LVEF (≥50%), after adjustment for LVESVi and RF, only ECV remained independently associated with symptoms (p = 0.046). Interestingly, when including the patients with a reduced LVEF < 50% in the multivariable analysis only LVESVi was an independent determinant of symptoms (p = 0.04) and ECV was not (p = 0.07) Conclusion: myocardial fibrosis quantified by ECV calculation is a determinant of symptoms in AR with preserved LVEF. Further studies are warranted to determine the prognostic value of ECV that may justify earlier intervention.